Comparison of coproprevalence and seroprevalence to guide decision-making in national soil-transmitted helminthiasis control programs: Ethiopia as a case study. - Sara Roose; Gemechu Tadesse Leta; Johnny Vlaminck; Birhanu Getachew; Kalkidan Mekete; Iris Peelaers; Peter Geldhof; Bruno Levecke (Public Library of Science (PLoS), 2022)
Background WHO recommends periodical assessment of the prevalence of any soil-transmitted helminth (STH) infections to adapt the frequency of mass drug administration targeting STHs. Today, detection of eggs in stool smears (Kato-Katz thick smear) remains the diagnostic standard. However, stool examination (coprology) has important operational drawbacks and impedes integrated surveys of multiple neglected tropical diseases. Therefore, the aim of the present study was to assess the potential of applying serology instead of coprology in STH control program decision-making. Methodology An antibody-ELISA based on extract of Ascaris lung stage larvae (AsLungL3-ELISA) was applied in ongoing monitoring activities of the Ethiopian national control program against schistosomiasis and soil-transmitted helminthiasis. Blood and stool samples were collected from over 6,700 students (median age: 11) from 63 schools in 33 woredas (districts) across the country. Stool samples of two consecutive days were analyzed applying duplicate Kato-Katz thick smear. Principal findings On woreda level, qualitative (seroprevalence) and quantitative (mean optical density ratio) serology results were highly correlated, and hence seroprevalence was chosen as parameter. For 85% of the woredas, prevalence based on serology was higher than those based on coprology. The results suggested cross-reactivity of the AsLungL3-ELISA with Trichuris. When extrapolating the WHO coproprevalence thresholds, there was a moderate agreement (weighted κ = 0.43) in program decision-making. Using the same threshold values would predominantly lead to a higher frequency of drug administration. Significance This is the first time that serology for soil-transmitted helminthiasis is applied on such large scale, thereby embedded in a control program context. The results underscore that serology holds promise as a tool to monitor STH control programs. Further research should focus on the optimization of the diagnostic assay and the refinement of serology-specific program decision-making thresholds.